MENGGUNAKAN KONSEP “AT-TURĀṠ WA AT-TAJDĪD” DALAM PEMIKIRAN HASSAN HANAFI UNTUK MENGATASI KEMISKINAN DI INDONESIA - Yuli Andriansyah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2015)
Considering that the poverty becomes the critical issue in almost all Muslim countries, it is crucial if the issue and its solution are exposed and discussed. To discuss the poverty and its solution, this article concerns to one of approaches stated by Hasan Hanafi. According to him, the poverty can be solved by increasing the individuals and private companies participations, which is in this case the business world is demanded to be more active in helping and developing the living quality of poor citizens. The role of the individuals and private companies in alleviating the poverty is the significant aspect which helps the government program to tackle the poverty problem. This article also suggests the role of the government to support the individuals and private companies to help the poor citizens. The incentive can be given to individuals or the companies which actively involve in the poverty alleviation program. The implementation of Hasan Hanafi’s idea about at-turāts wa at-tajdīd is proven to be effectively applied even though it has many challenges.